Biodegradation of textile dyes by bacteria isolated from textile industry effluents - Aktar, Khusbu; Zerin, Tamanna; Banik, Avijit (Stamford Journal of Microbiology, 2020)
A country like Bangladesh where textile industries are the main source of developing economy, pollution problem from such industries creates a huge risk for the environment. Textile industries discharge a huge amount of effluent containing various harmful chemicals including synthetic dyes that are very stable and threat to the living organisms. This study deals with the potential decolorization and biodegradation of Bemacron Yellow HP-2R (BY), Bemacron Red RS (BR) and Bemacron blue RS 01 (BB) dyes using bacteria isolated from textile effluent. The effluent and soil samples were collected from different locations of discharge point. Only two isolates were screened out after primary screening using dye supplemented nutrient agar media. Following colony morphology, physiology and biochemical analysis, they were presumptively identified as Bacillus sp. and Staphylococcus aureus. They were subjected to decolorization of 0.002 g/l BY, BR and BB dyes. Bacillus sp. showed superior decolorization potential of BR (71%) and BB (83%) dyes after 5 days of incubation. Whereas, Staphylococcus aureus showed 79% decolorization of BY dye after 5 days incubation. Decolorization efficacy can be further improved by optimizing environmental conditions and process parameters. Stamford Journal of Microbiology, Vol.9(1) 2019: 5-8